2018
DOI: 10.1017/s1743923x18000235
|View full text |Cite
|
Sign up to set email alerts
|

Thriving or Dividing? The Women's Movement and the Independence Referenda in Scotland and Catalonia

Abstract: Territorial debates have recently shaken the political systems in Scotland and Catalonia, leading to referenda on independence. This article engages with questions concerning whether this extraordinary process has affected the women's movement and why. Specifically, feminist scholars have often expressed concern regarding how strong territorial identities and nationalist projects might prove detrimental to the movement's unity and success. Here, I look for indications of engagement and revival within the frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Feminist struggles have grown out of the experience of joint political democratic and anti‐austerity projects with other civil society groups. The resurgence of civil society activism that exploded with the Indignados movement, the experience of local political activism in grassroots organizations and citizens' waves, and the participation in anti‐austerity struggles have empowered and revitalized the Spanish feminist movement, making it more effective in the organization and representation of women's interests than former research had found (Alonso, ; Bustelo, ; Clavero, ; García, ; Valiente, ). The successful outcome of feminist pro‐abortion mobilizations — i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feminist struggles have grown out of the experience of joint political democratic and anti‐austerity projects with other civil society groups. The resurgence of civil society activism that exploded with the Indignados movement, the experience of local political activism in grassroots organizations and citizens' waves, and the participation in anti‐austerity struggles have empowered and revitalized the Spanish feminist movement, making it more effective in the organization and representation of women's interests than former research had found (Alonso, ; Bustelo, ; Clavero, ; García, ; Valiente, ). The successful outcome of feminist pro‐abortion mobilizations — i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The feminist movement mobilized strongly against what it renamed a ‘counter‐reformist’ bill, by organizing huge demonstrations, reactivating organizations such as the National Platform of Feminist Organizations, and forging national and international alliances (Alonso, ; García, ). The struggle to defend the right of abortion was a success story for the feminist movement.…”
Section: Spain's Policy Making In Response To the Crisis: Changes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Este ha experimentado un claro incremento en su nivel de movilización, con la creación de nuevas estructuras y una mayor coordinación a nivel estatal, hecho que no había ocurrido en décadas, dado el elevado nivel de fragmentación territorial del mismo (Lombardo, 2016;Alonso, 2016;García, 2015). Este auge del movimiento ha de entenderse en el marco del mayor ataque a los derechos sociales y reproductivos de las mujeres españolas en la etapa democrática.…”
Section: Políticas En Materia De Derechos Sexuales Y Reproductivos Enunclassified
“…Meanwhile, in North Sumetera, there were around 15,000 people killed, including Chinese ethnic, and around 15,000 others were arrested [2]. It caused [3] bitter experience or traumatic event often haunts the journey of human life. Although it has been buried deeply, bad events at certain moments can be recalled.…”
Section: Introductionmentioning
confidence: 99%